The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fmicb.2022.942940
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Antifungal Resistance of Cryptococcus neoformans From Human Immunodeficiency Virus-Negative and Human Immunodeficiency Virus-Positive Patients in Eastern China

Abstract: Cryptococcosis is an opportunistic and potentially lethal infection caused by Cryptococcus neoformans and Cryptococcus gattii complex, which affects both immunocompromised and immunocompetent people, and it has become a major public health concern worldwide. In this study, we characterized the molecular epidemiology and antifungal susceptibility of 133 C. neoformans isolates from East China Invasive Fungal Infection Group (ECIFIG), 2017–2020. Isolates were identified to species level by matrix-assisted laser d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Using genome assemblies, Mashtree was used to reconstruct the phylogenetic tree efficiently. Not only can CNSCs and CGSCs be clearly distinguished, but subclusters in the major cluster can also be classified, as reported by Ziyi Zhou et al in 2022 in a study that showed that ST5 has different subtypes based on the detection of single nucleotide polymorphism (SNPs) variants ( Zhou et al, 2022 ), and the ST5 cluster and ST31 cluster can be roughly considered CC5 and CC31 ( Fan et al, 2016 ; Cogliati et al, 2019 ; Thanh et al, 2019 ). Furthermore, the relationship between AD hybrids and other CCs could be clearly distinguished.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Using genome assemblies, Mashtree was used to reconstruct the phylogenetic tree efficiently. Not only can CNSCs and CGSCs be clearly distinguished, but subclusters in the major cluster can also be classified, as reported by Ziyi Zhou et al in 2022 in a study that showed that ST5 has different subtypes based on the detection of single nucleotide polymorphism (SNPs) variants ( Zhou et al, 2022 ), and the ST5 cluster and ST31 cluster can be roughly considered CC5 and CC31 ( Fan et al, 2016 ; Cogliati et al, 2019 ; Thanh et al, 2019 ). Furthermore, the relationship between AD hybrids and other CCs could be clearly distinguished.…”
Section: Discussionmentioning
confidence: 93%
“…in 2022 in a study that showed that ST5 has different subtypes based on the detection of single nucleotide polymorphism (SNPs) variants (Zhou et al, 2022), and the ST5 cluster and ST31 cluster can be roughly considered CC5 and CC31 (Fan et al, 2016;Cogliati et al, 2019;Thanh et al, 2019). Furthermore, the relationship between AD hybrids and other CCs could be clearly distinguished.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Our reported AMB MIC trend has been described in other studies outside the United States. [35][36][37] In one study that evaluated the MIC distribution of different antifungal agents against Cryptococcus isolates collected from clinical and environmental samples from different countries before 1980 (prior to the HIV epidemic), 71.2% of C.…”
Section: Discussionmentioning
confidence: 99%